Linfoma de celulas grandes T anaplásico: experiencia de 10 años en el Instituto Nacional de Enfermedades Neoplásicas, Lima - Perú - Pacheco-Román, C (2022)
Introduction: Anaplastic Large T cells Lymphoma is a rare pathology, determined by expression of CD30 and differences in presentation and aggressiveness according to the ALK expression. Objectives: This study seeks to determine the epidemiological, clinicopathological and prognosis of patients with Anaplastic Large T-cell Lymphoma. Methods: The clinical records of patients diagnosed with Anaplastic Large T cells Lymphoma from the National Institute of Neoplastic Diseases in Lima-Peru were analyzed between years 2006 to 2016. Results: Of 86 patients, 57% were male, 21.9% were positive for ALK, 48 patients were found in clinical stage I and II and 36 between stages III and IV. 57 patients had low or low intermediate risk while 26 patients were between high and high intermediate risk. The estimated overall survival was 40.8% at 5 years. In patients with positive ALK group was 67.4% and in the group with negative ALK was estimated at 30.2%. Conclusions: Anaplastic Large T Cells Lymphoma is an important aggressive disease with heterogeneous distribution for age and slightly more common in males, with the expression of ALK and international prognostic index as important prognostic factors.